How Formed the Self-Esteem of People who Grew up in Typical Families and People who Grew up in Families with Separated Parents and the IPA as a Means of Analysis of this Phenomenon - Simoni Chrysoula (2014)
Divorced Family, Typical Family, Self-Esteem, IPA, Self-Confidence.